2004
DOI: 10.1007/s00586-004-0802-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the paraspinal approach to the lumbar spine

Abstract: The original description of the paraspinal posterior approach to the lumbar spine was for spinal fusion, especially regarding lumbosacral spondylolisthesis treatment. In spite of the technical details described by Wiltse, exact location of the area where the sacrospinalis muscle has to be split remains somewhat unclear. The goal of this study was to provide topographic landmarks to facilitate this surgical approach. Thirty cadavers were dissected in order to precisely describe the anatomy of the trans-muscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 11 publications
0
44
0
2
Order By: Relevance
“…from the midline for the natural cleavage plane. 3,4 When skin incisions are made a set distance from the mid-line, access to the facet joint and pars is compromised due to mismatch between the position of the skin incision and that of the cleavage plane.…”
Section: Introductionmentioning
confidence: 99%
“…from the midline for the natural cleavage plane. 3,4 When skin incisions are made a set distance from the mid-line, access to the facet joint and pars is compromised due to mismatch between the position of the skin incision and that of the cleavage plane.…”
Section: Introductionmentioning
confidence: 99%
“…7,36 One of the potential limitations of the Wiltse approach is that central decompression is technically more difficult to achieve, but this is overcome as one gains familiarity with the approach. 30,31 There are numerous studies that have evaluated the effect of dissection time and extent of surgical retraction during midline spine surgery on local muscle function, vascularity, and viability. Studies in animals and humans have consistently shown that prolonged paraspinal muscle retraction predisposes patients to increased pain and a higher degree of tissue necrosis and puts them at a potentially greater risk of infection.…”
mentioning
confidence: 99%
“…Having used for some 30 years the approach (Wiltse) it might be thought that this paper by Vialle et al [36] had little to teach me. However, I had often been struck by the variability in terms of bleeding and ease of dissection of the approach as I did it.…”
Section: Paraspinal Approach To the Lumbar Spinementioning
confidence: 99%